Blood or Serum Exposure Induce Global Transcriptional Changes, Altered Antigenic Profile, and Increased Cytotoxicity by Classical Bordetellae - Gestal, Monica C.; Rivera, Israel; Howard, Laura K.; Dewan, Kalyan K.; Soumana, Illiassou Hamidou; Dedloff, Margaret; Nicholson, Tracy L.; Linz, Bodo; Harvill, Eric T. (Frontiers in Microbiology, 2018)
The classical bordetellae sense and respond to a variety of environments outside and within their mammalian hosts. By causing inflammation and tissue damage, we reasoned that bordetellae are likely to encounter components of blood and/or serum during the course of a respiratory infection, and that detecting and responding to these would be advantageous. Therefore, we hypothesized that classical bordetellae have the ability to sense and respond to blood or serum. Blood or serum exposure resulted in substantial transcriptional changes in Bordetella bronchiseptica, including enhanced expression of many virulence-associated genes. Exposure to blood or serum additionally elicited production of multiple antigens not otherwise detectable, and led to increased bacterial cytotoxicity against macrophages. Transcriptional responses to blood/serum were observed in a Bvg‒ phase-locked mutant, indicating that the response is not dependent on a functional BvgAS system. Similar transcriptional responses to blood/serum were observed for the other classical bordetellae, Bordetella pertussis and Bordetella parapertussis. These data suggest the classical bordetellae respond to signals present in blood and serum by changing their behavior in ways that likely contribute to their remarkable success, via effects on pathogenesis, persistence and/or transmission between hosts.